Trans-stenotic pressure gradient as derived from CT improves patient management: ADVANCE registry. (14th October 2021) - Takagi, H; Fairbairn, T; Akasaka, T; Norgaard, B; Berman, D; Raff, G; Hurwitz-Koweek, L; Pontone, G; Kawasaki, T; Sand, N; Jensen, J; Amano, T; et al.
Abstract: Background: The change in fractional flow reserve derived from CT (FFRCT) value across a coronary stenosis (ΔFFRCT) improves the physiological characterization of coronary artery disease (CAD). The role of ΔFFRCT in guiding risk-stratification and downstream testing in patients with stable CAD is unknown. Purpose: To investigate the incremental value of ΔFFRCT at predicting early revascularization and improving efficacy of resource utilization. Methods: Patients with CAD on CT coronary angiography (CTCA) were enrolled in an international multicenter registry. Patients with non-evaluable FFRCT analysis were excluded. The CTCA was assessed for: stenosis severity as per CAD-Reporting and Data System (CAD-RADS), lesion length and lesion-specific FFRCT measured 2 cm distal to stenosis. Risk factors and actual treatment (revascularization vs medical therapy) at 90-day follow-up were recorded. Multivariable logistic regression analysis for early revascularization was conducted. The incremental discrimination for revascularization prediction was compared among 3 models (model 1: risk factors + lesion length and location + CAD-RADS; model 2: model 1 + lesion-specific FFRCT; model 3: model 2 + ΔFFRCT). Simulating ICA referral for patients with CAD-RADS ≥3 and lesion-specific FFRCT ≤0.8, the potential impact of ΔFFRCT at reducing ICA referral and improving the ratio of subsequent revascularization was assessed. Results: Of 4730 patients (66±10 years; 34% female), 2092 (42.7%) underwent ICA and 1168 (24.7%) underwent early revascularization. With increasing ΔFFRCT, a higher incidence of revascularization (Figure 1A) and an increase in the revascularization to ICA ratio was observed (Figure 1B). ΔFFRCT >0.13 was the optimal cut-off for predicting revascularization as determined by the Youden index. ΔFFRCT remained an independent predictor for early revascularization (odds ratio per 0.05 increase with 95% CI, 1.31 [1.26–1.35]; p<0.0001) after adjusting for risk factors, CAD-RADS, lesion length and location, and FFRCT. Among the 3 models, model 3, which included ΔFFRCT showed the highest AUC and improved discrimination power compared to model 2 (0.87 [0.86–0.88] vs 0.85 [0.84–0.86]; p<0.0001] (Figure 2), with the greatest incremental value for ΔFFRCT observed in patients with lesion-specific FFRCT between 0.71–0.80. In patients with CAD-RADS ≥3 and lesion-specific FFRCT ≤0.8, a diagnostic strategy incorporating ΔFFRCT >0.13 would potentially reduce ICA referral by 32.2% (1638 to 1110) and improve the revascularization to ICA ratio from 65.2% [1068/1638] to 73.1% [811/1110]. Conclusions: The characterization of CAD with ΔFFRCT improves the identification of patients requiring early revascularization as compared to a standard diagnostic strategy of CTCA with FFRCT, particularly for those with lesion-specific FFRCT of 0.71–0.80. ΔFFRCT has the potential to aid decision making for ICA referral and improve the efficiency of resource utilization. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): HeartFlow, Inc., Redwood City, CA, USA